(untitled) (Linguostylistic Studies, 2015)
A concept «Scientific text» is considered in the article. The criteria of determination of whole text as units of commonunication are distinguished. The basic going of the analysis of scientific text is described. The basic aspects of research of scientific text are certain. The looks of many Ukrainian and foreign scientists are reasonable to understanding of text as a level of the language system. The features of the cognitive going are exposed near the analysis of text. The role of the functionally-stylistic going is distinguished near the study of scientific text, synergetics going near consideration of the thinking processes presented in scientific text. Facilities of expression of dialogic nature of text are certain. Key words: scientific text, organization of text, language system, language organization of text, communicative situation. References